MANAJEMEN PENGEMBANGAN KOMPETENSI GURU BERBASIS KEBUTUHAN SEKOLAH (Studi Kasus Pada Guru-guru SMP Avicenna Jakarta dan Depok Yayasan Pendidikan Avicenna Prestasi) - Wawan Karsiwan, Wawan (2020)
This research aims to explore the effectiveness of competency development program in accordance with the needs of school development. The effectiveness of the Teacher Competency Development program, one of which is determined by the process of necessity analysis, so that the development of the program which was implemented could fulfill the primary needs of the schools and teachers. Therefore, it is important to manage teacher competency development program effectively. The research method used in this study is mixed-method, in which the research is excavated research problems with two types of data, both qualitative and quantitative. Specifically, the mixed method used here is the sequential explorative method, wherein this study the stage of data collection was firstly done in advance with a qualitative approach, then followed by quantitative approached, and lastly finished with a qualitative approach again to interpret the results of this research. Some of the data collection techniques that are used were Interview with guidelines, questionnaires, Self-assessment inventory, observation, focus group discussion, and documents which are related to teacher development policy. The research samples that become the source of data in this research consist of several parties, namely: the social foundation as the founder and manager of SMP Avicenna, principal of SMP Avicenna Jakarta and Depok, and junior secondary school teachers of Avicenna Jakarta and Depok. Data analysis is done qualitatively and quantitatively. Through the Trials of competency development management model based on school needs that have been developed, it obtained the results that there is an increase in competence of 26 participants from the total participants as many as 30 people. While two participants showed similar results, both pre and trial models. Moreover, there were only two participants who have decreased. Through observation, it could be seen in some aspects of observation that the participants showed readiness in the training program, the process of group dynamics occurred during the training program by conducting a role division, and the participants felt comfortable during the training program with vigorously. At the end of the implementation of the model trials through this training, each group was able to produce products.